Biochar as an organic source for soil carbon sequestration in acidic soil of Kerala - K, RAJALEKSHMI (Journal of Soil and Water Conservation, 2019)
Soil organic matter (SOM), a determinant of soil health, is highly responsive to global warming. Soil organic matter improves and stabilizes the soil structure which in turn can hold large amounts of water, thus leading to significant reduction in surface runoff and soil erosion. Biochar, a charcoal produced by pyrolysis of biomass food stock (eg. plant material), may be a substantial solution in reducing global warming. It is an excellent soil amendment that offers a cheap, easily accessible source of organic carbon (OC) which improves water retention as well as microbial activity. An experiment was conducted in wetland ecosystem (Ultisol) with the aim to improve the stabilisation of added soil C during rice crop for two continuous seasons, kharif and rabi. The treatments consisted of control and four different organic sources [Farmyard manure (FYM), green manure (daincha), Artocarpus leaves and rice husk biochar (RHB)] in combination with inorganic nitrogen viz., urea at various levels such as no inorganic nitrogen, 35 kg N ha-1, 70 kg N ha-1 and 105 kg N ha-1. The RHB treatment recorded maximum value for SOC in both seasons (1.67 and of 2.05%). The SOC values had a decreasing trend as a whole in the second season, but the values were comparatively higher in the RHB treatment. It was also noticed that the SOC content in organic sources was obviously higher than the control treatment and through conversion to biochar, up to 50% of the initial biomass C can be sequestered. The highest values of organic carbon in biochar treated soils indicated the presence of recalcitrant organic carbon in biochar. Application of biochar increased maximum allocation of carbon both in the soil and in biomass, thus portraying the C sink capacity. Conversion to organic agricultural practices with biochar application can help in restoring the eco-system resilience without compromising food productivity.